Компресивні способи утворення назв продуктів програмного забезпечення - Юшак, Вікторія Миколаївна; Yushak, V. M. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті зроблено спробу визначити роль компресії у словотворенні, за допомогою якої реалізується закон мовної економії. Компресія розглядається як засіб підвищення інформативності й експресивності новоутворених лексичних одиниць. Виявлено, що в утворенні назв продуктів програмного забезпечення використовуються такі компресивні способи: абревіація, усічення, телескопія, еліпсис, словоскладання, заміна слів цифрами, упущення букв. З’ясовано, що найпродуктивнішим способом компресивного словотворення є абревіація, яка, крім номінативної, може виконувати експресивну й індивідуалізуючу функції. The article is concerned with the compressive ways of word-formation of software products names. The study is an attempt to define the role of compression in word-formation. Compressiveness is viewed as one of the main characteristics of the software products names. The following compressive ways of formation of the names are defined: abbreviation, clipping, blending, ellipsis, replacing of words with numbers, omission of letters. The reasons for the use of the compressive types are their time and space efficiency, the frequency of use of program types and formats. Compression is a means of intensifying of informativity and expressiveness of lexical units. The characteristic features of the compressive ways are diversity, variability and combinability. Special attention is paid to the analysis of abbreviations, which except the nominative can perform individualizing and expressive functions.
Compressive Methods of Formatio of the Names of Products of Software
Keywords: назва; name; мовна економія; language economy; компресія; compression